Roux-en-Y Gastric Bypass Decreases Serum Inflammatory Markers and Cardiovascular Risk Factors in Obese Diabetics - Rossi, Isolina (Surgery, 2020)
BACKGROUND: Obesity and type 2 diabetes mellitus (T2DM) are associated with elevated levels of inflammatory markers. This chronic inflammation is known to contribute to increased risk of cardiovascular disease (CVD) in these populations. Laparoscopic Roux-en-Y gastric bypass (LRYGB) is associated with a high rate of diabetes remission. We hypothesize that LRYGB decreases systemic inflammatory markers and CVD risk factors in obese diabetics. METHODS: Single-institution prospective cohort study of 61 obese patients with T2DM. Thirty underwent LRYGB surgery and 31 underwent standard medical therapy with diabetes support and education. Collected data included pre- and post-operative inflammatory biomarkers and clinical parameters. RESULTS: Twelve months after undergoing LRYGB, after controlling for sex and age, there was a significant correlation between change in interleukin-6 (IL-6) and change in systolic blood pressure (SBP) (Spearman’s r=0.41, p=0.03). Similarly, when sex and age were controlled for in the LRYGB group, a statistically significant relationship remained between percent excess weight loss and change in IL6 (p=0.001). CONCLUSION: A significant relationship exists between decreased systemic IL-6 levels and both excess weight loss and lowered SBP after LRYGB in obese diabetics. These correlations may explain the decreased risk of cardiovascular disease after surgical weight reduction in this patient population.